ANALYSIS OF THE STRATEGY FOR DEVELOPING MSMES OF BANANA CHIPS FOOD SUPPLY CHAIN - Reni Yusnita; Selvira Wardani Tanjung; Siti Aisyah (Transpublika Publisher, 2022)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a fairly strategic role in the nation's economy. With one of the considerable potentials in the banana chip MSME center, it can be an opportunity in a business carried out by utilizing the supply chain. The supply chain in a business is very important to implement, where the availability and distribution of existing goods will greatly affect the sustainability of a business being run. This study aims to analyze the supply chain development strategy of banana chip food MSMEs by using an interactive model data analysis developed by Miles & Huberman. The results revealed that the supply chain development strategy of MSMEs in banana chip food includes product development, inventory, distribution and marketing, as well as consumers. Hence, an alternative supply chain model can be developed from the analysis of channel development and wider marketing distribution to dominate the existing market share in order to achieve the goals of a business run by a banana chip entrepreneur.